2014
DOI: 10.1158/0008-5472.can-13-2683
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Oncogenomics Identifies PSMB4 and SHMT2 as Potential Cancer Driver Genes

Abstract: Cancer genomes maintain a complex array of somatic alterations required for maintenance and progression of the disease, posing a challenge to identify driver genes among this genetic disorder. Toward this end, we mapped regions of recurrent amplification in a large collection (n ¼ 392) of primary human cancers and selected 620 genes whose expression is elevated in tumors. An RNAi loss-of-function screen targeting these genes across a panel of 32 cancer cell lines identified potential driver genes. Subsequent f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 44 publications
(45 reference statements)
2
111
0
2
Order By: Relevance
“…This upregulation at the protein level, along with that of SHMT2, is consistent with their elevated mRNA expression in various cancer types 45 . SHMT2 was implicated as a driver required for survival in a series of cancer cell lines 46 , and was shown to be upregulated and required for maintenance of redox balance and tumour cell survival in response to hypoxia 47 . Finally, in apparent contrast to its metabolism function in mitochondria, SHMT2 was recently identified as an adaptor subunit of a cytosolic BRISC (BRCC36 isopeptidase complex) deubiquitinase 48 .…”
Section: Articlementioning
confidence: 99%
“…This upregulation at the protein level, along with that of SHMT2, is consistent with their elevated mRNA expression in various cancer types 45 . SHMT2 was implicated as a driver required for survival in a series of cancer cell lines 46 , and was shown to be upregulated and required for maintenance of redox balance and tumour cell survival in response to hypoxia 47 . Finally, in apparent contrast to its metabolism function in mitochondria, SHMT2 was recently identified as an adaptor subunit of a cytosolic BRISC (BRCC36 isopeptidase complex) deubiquitinase 48 .…”
Section: Articlementioning
confidence: 99%
“…These include DHFR (dihydrofolate reductase), an enzyme strongly inhibited by current antifolates, and TYMS (thymidylate synthase), the target of the important chemotherapeutic 5-fluorouracil (Huennekens, 1994;Longley et al, 2003). Equally upregulated are two genes of mitochondrial 1C transformations: SHMT2 (mitochondrial serine hydroxymethyl transferase) and MTHFD2 (mitochondrial methylenetetrahydrofolate dehydrogenase) (Jain et al, 2012;Lee et al, 2014;Nilsson et al, 2014). Together these enzymes, both of which lie in a pathway essential for embryonic development (Di Pietro et al, 2002;Momb et al, 2013), transform serine into glycine and a formyl unit attached to THF (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…A recent metastudy including microarray data from more than 1,900 tumor tissues of 19 different cancer types suggested that the mitochondrial 1-carbon metabolism is the most deregulated metabolic pathway in human cancers (20). Intriguingly, SHMT2 and MTHFD2 were found to be overexpressed in multiple human cancers and were correlated with shorter survival in breast cancer patients (16,20,21). Knockdown of MTHFD2 in breast cancer cells suppressed proliferation and induced apoptosis (20).…”
Section: Introductionmentioning
confidence: 99%